Unit cohesion and warfare in the ancient world
1 online resource
Keywords: "This book explores unit cohesion in ancient armies, and how this contributed to the making of war in the Mediterranean world. It takes a varied approach to the subject, from looking at individual groups within larger armies to juxtaposing vertical and horizontal types of cohesion, providing a more detailed understanding of how groups were kept together. Within the broader definition of 'unit cohesion', this volume approaches more specific aspects of military cohesion in the ancient Mediterranean world including how individual soldiers commit to one another; how armies and units are maintained through hierarchy and the 'chain of command'; and social cohesion, in which social activities and aspects of social power help bind an army or unit together. Examples from across the ancient Mediterranean are explored in this volume, from Classical Greece to Late Antiquity, with topics such as how armies and units cohere during the sacking of cities, Roman standards as a focus of religious cohesion, and how the multi-ethnic mercenary armies of Carthage cohered. Modern approaches to social cohesion are deployed throughout, and these essays serve as an important complement to existing literature on unit cohesion more generally. Unit Cohesion and Warfare in the Ancient World is of interest to students and scholars of ancient warfare, military history and military studies, as well as those working on the ancient Mediterranean world more broadly"--